Combined EGFR/MEK Inhibition Prevents the Emergence of Resistance in EGFR mutant Lung Cancer - Tricker, Erin M. (Cancer Discov, 2015)
Irreversible pyrimidine based EGFR inhibitors, including WZ4002, selectively inhibit both EGFR activating and EGFR inhibitor resistant T790M mutations more potently than wild type EGFR. While this class of mutant selective EGFR inhibitors is effective clinically in lung cancer patients harboring EGFR T790M, prior preclinical studies demonstrate that acquired resistance can occur through genomic alterations that activate ERK1/2 signaling. Here we find that ERK1/2 reactivation occurs rapidly following WZ4002 treatment. Concomitant inhibition of ERK1/2 by the MEK inhibitor trametinib prevents ERK1/2 reactivation, enhances WZ4002 induced apoptosis and inhibits the emergence of resistance in WZ4002 sensitive models known to acquire resistance via both T790M dependent and independent mechanisms. Resistance to WZ4002 in combination with trametinib eventually emerges due to AKT/mTOR reactivation. These data suggest that initial co-targeting of EGFR and MEK could significantly impede the development of acquired resistance in mutant EGFR lung cancer.